ATLANTOAXIAL INSTABILITY IN CHILDREN WITH DOWN SYNDROME - CATARINA MASSANO; JOANA PÁSCOA PINHEIRO; JOÃO PEDRO; PEDRO FERNANDES (Coluna/Columna, 2025)
ABSTRACT Atlantoaxial instability (AAI) occurs in 10 to 30% of Down Syndrome (DS) patients, with symptomatic disease ranging from 1 to 2%. Based on a rare clinical case, this article aims to highlight the main aspects of AAI screening and treatment. The authors report the case of a 4-year-old patient with DS who presented with quadriparesis after minor cervical trauma. Imaging studies revealed atlantoaxial dislocation associated with os-odontoideum (OsO). The patient was submitted to posterior C1-C2 arthrodesis (Harms technique) with an iliac bone graft. At three months post-surgery, the patient exhibited complete neurological recovery and remained neurologically intact and asymptomatic over the actual 10 years of follow-up. This case report highlights the importance of screening DS patients for myelopathic signs and symptoms. Cervical imaging should be reserved for symptomatic patients and surgery for patients with neurological compromise or an atlanto-dens interval superior to 10mm. When warranted, stable fixation with posterior screws appears to be the surgical technique of choice. Level of Evidence V; Case Report.